Conflict Management Strategies in Project Teams to Improve Collaboration and Productivity - Syarif, Nurliana (Generasi Sains Indonesia, 2024)
Effective conflict management is essential for enhancing collaboration and productivity within project teams. This study investigates the types of conflicts prevalent in project settings specifically task-related, interpersonal, and process-related conflicts and explores the impact of various conflict management strategies on team performance. Through a qualitative case study approach, data was gathered from multiple project teams across different industries, highlighting how collaborative conflict management positively influences team dynamics and project outcomes. The results show that task-related conflicts, when addressed collaboratively, contribute to improved team cohesion and productivity. However, process-related conflicts often require a more structured approach, as collaborative methods alone may not fully resolve procedural disagreements. This study supports the notion that tailored conflict management approaches are necessary for optimal team performance and project success.